Biosimilars: the process is the product. The example of recombinant streptokinase. (31st July 2014) - Thelwell, C.; Longstaff, C.
Summary Background Worldwide, streptokinase remains the most used thrombolytic agent for the treatment of myocardial infarction. Recombinant streptokinase, from E. coli, is increasingly used in developing countries as a biosimilar of native streptokinase; however, potency assignments relative to the WHO International Standard (IS) are highly variable with potentially dangerous consequences. A proportion of recombinant streptokinase appears to be incompletely processed, retaining the amino‐terminal methionine engineered for intracellular expression. Objectives To investigate and quantify the impact of an amino‐terminal methionine on streptokinase activity. Methods Mature native streptokinase (rSK) was cloned and a novel variant constructed to include an amino‐terminal methionine (rSK‐Met) that is not susceptible to processing during expression. Potencies of rSK and rSK‐Met were determined relative to the WHO IS using a chromogenic solution (European Pharmacopoeia) assay, and fibrin‐based assays. Results In the chromogenic solution assay there was no measurable difference between rSK and rSK‐Met activities. In the fibrin‐based methods, however, potency estimates for rSK‐Met were greatly reduced compared with rSK, and fibrinolytic activity for rSK‐Met was shown to increase over time with methionine aminopeptidase treatment. This apparent difference in activity and fibrin selectivity was consistent with potency estimates for several different batches of commercial recombinant streptokinase products also tested; consequently, different potencies would be assigned to therapeutic recombinant streptokinase products depending on the degree of amino‐terminal methionine processing, and on the pharmacopoeial assay method used, affecting the dosage patients receive. This has serious health implications and provides an example of the danger in the unregulated clinical use of biosimilars.